How gender affects the buying-decision process among consumers of luxury goods - Marques, S. (2019)
Over the decades, many studies focused on luxury brand consumption and explored the customer perception and motives for purchasing luxury brands. Nevertheless, the role of gender in this context has been neglected. Recently, some researchers have been studying the influence of gender on luxury purchases. However, the subject is not fully explored and the effect of some motivations are still lacking on the studies. The present dissertation is based on previous researches about luxury values, consumer behaviour and gender behavioural differences. The study aimed to contribute to the analysis of whether men and women buy luxury for different reasons, from which the following research questions arise: Does gender have an effect on the purchase of luxury goods? And how does gender affect the buying-decision process among consumers of luxury goods? In order to answer these questions, a documentary analysis was conducted, as well as a face-to-face questionnaire to Portuguese women and men that buy ready-to-wear and/or luxury accessories. Results revealed that different motivations are attributed to each gender; in other words, women and men buy luxury products for different reasons. It was established that women have a higher purchase intention than men and respond more favourably to luxury brands promotional activity. Furthermore, men showed to be motivated by materialistic value, status value and conspicuous value, responding more positively to luxury brands loyalty programs than females. Nevertheless, gender did not show an effect on hedonic value, susceptibility to normative influence and uniqueness value.